Prevention of Motile Aeromonas Septiceamia in Striped Catfish (Pangasianodon hypophthalmus) using Cherry Leaf Solution - Riski Mutia Sari; Iesje Lukistyowati; Morina Riauwaty (Jurnal Perikanan dan Kelautan, 2022)
This research was conducted in December 2019 – February 2020 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Universitas Riau. The purpose of this study was to analyze and obtain the best dose of cherry leaf (Muntingia calabura) solution to prevent Motile Aeromonas Septicemia from total leukocytes, leukocyte differentiation, and phagocytic activity of striped catfish (Pangasianodon hypophthalmus). The method used is an experiment with a completely randomized design (CRD) one factor five levels of treatment. The doses used were negative control (without immersion cherry leaf solution and not infection with Aeromonas hydrophila), positive control (without immersion cherry leaf solution and infection with A.hydrophila), P1 (Immersion in cherry leaf solution at a dose of 2800 ppm), P2 (3,200 ppm), and P3 (3,600 ppm). Immersion was carried out 5 times for 5 minutes with an interval of 7 days. The results showed that immersion with cherry leaf solution at a dose of 3,600 ppm (P3) was the best dose (P<0.05) with a total leukocyte value of 10.66 x 104 cells/mm3, lymphocytes 84.67%, monocytes 5.67%, neutrophils 9.67%, phagocytic activity 36.67%, and survival rate 86.67%